TOURISTS’ REVISIT INTENTIONS TO KEBUMEN: DESTINATION IMAGE REVIEW - Rahmawati, Esti Dwi; Prastiwi, Putri Intan; Fadila, Sarah; Baaq, Shalli Habiibika (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
This study aims to analyze the influence of three dimensions of destination image, namely cognitive image, affective image, and unique image on tourists' intention to revisit Jatijajar Cave tourist destination in Kebumen. A quantitative approach was used in this study with a survey method and data analysis using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data were obtained from 100 respondents who had previously visited the destination. The results showed that the three dimensions of destination image significantly and positively influence revisit intention, with unique image making the largest contribution. The findings provide important implications for tourist destination managers in improving attractiveness and tourist experience through appropriate marketing strategies. This study also identified some limitations, such as not considering the impact of the COVID-19 pandemic. Managerial recommendations include improving facilities and managing tourist areas to increase visitor comfort.